1978
DOI: 10.1002/pssa.2210450132
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction study of anharmonic thermal vibrations in CuCl

Abstract: The effect of noncentrosymmetric anharmonic vibrations of atoms in cuprous chloride is investigated by X‐ray diffraction on a single crystal at room temperature. The observed structure factors are found to be sufficiently sensitive to anharmonic vibrations of atoms and the parameters of the effective one‐atom potential fields are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This has indeed been found for ZnX where X --S, Se, Te (McIntyre, Moss & Barnea, 1980). Different anharmonic parameters of the cation and anion were only evaluated in the case of the A~B TM compounds near the zinc blende to NaCl phase transition by Harada (1976) for CuBr and by Valvoda & Je~n~, (1978) for CuC1. It is impossible, however, to distinguish between flGa and ~gs with the present method.…”
Section: Discussionmentioning
confidence: 60%
“…This has indeed been found for ZnX where X --S, Se, Te (McIntyre, Moss & Barnea, 1980). Different anharmonic parameters of the cation and anion were only evaluated in the case of the A~B TM compounds near the zinc blende to NaCl phase transition by Harada (1976) for CuBr and by Valvoda & Je~n~, (1978) for CuC1. It is impossible, however, to distinguish between flGa and ~gs with the present method.…”
Section: Discussionmentioning
confidence: 60%
“…Colella (1971), Barnea, Mclntyre & Moss (1974) and Bilderback & Colella (1976) have observed Bijvoet differences in low-angle reflections, due to bonding in different ZnS-type structures. Mclntyre, Moss, Boehm & Barnea (1975) and Valvoda & Jecny (1978) have reported Bijvoet differences for high-angle reflections where anharmonic effects are appreciable for ZnSe and CuCI respectively.…”
Section: Anomalous Dispersion Effectsmentioning
confidence: 98%
“…However, a few X-ray works have also been reported as reviewed by McIntyre et al [l], who have reported anharmonic thermal vibrations in a flat plate ZnSe single I ) Madurai 625021, India. [3] have reported the refinement of individual anharmonic thermal parameters in GaAs,,,,,P,,,,, and CuC1, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…crystal. Mohanlal and Pathinettampadiyan [2] and Valvoda and JeEny [3] have reported the refinement of individual anharmonic thermal parameters in GaAs,,,,,P,,,,, and CuC1, respectively.…”
Section: Introductionmentioning
confidence: 99%